Exploration the Potency of Copper and Dyes Multi-Resistant of Indigenous Bacteria Isolated from Cikijing River, West Java - Wahyu Irawati; Reinhard Pinontoan; Triwibowo Yuwono; Indah Sofiana; Valentine Lindarto; Dwi Ningsih Susilowati (Journal of Tropical Biodiversity and Biotechnology, 2025)
Various types of textile dye have been reported to contaminate the Cikijing River, West Java, Indonesia due to its location within the industrial region of Rancaekek District. It has been understood that certain bacterial species develop copper resistance and dye decolourisation as a mechanism of stress adaptation. The study aims at isolating and characterising copper and dye resistance as well as decolourisation ability of bacteria isolated from the Cikijing River. Copper-resistant bacteria were isolated using a series dilution method on Luria Bertani media supplemented with the addition of 1-10 mM CuSO4. Purified bacterial isolates were then tested for copper resistance onto LB agar medium supplemented with CuSO4 concentrations ranging from 0 mM to 20 mM and decolourisation of various dyes. A total of 59 copper-resistant bacteria were successfully isolated, nine of them showed the highest copper resistance with a MIC value from 11 mM up to 16 mM CuSO4 and resistance to 4 types of dyes up to 700 ppm. The 16S rDNA analysis showed that the nine isolates were Klebsiella sp., Klebsiella pneumoniae, Lysinibacillus boronitolerans, Lysinibacillus fusiformis, Bacillus proteoliticus, Pseudomonas stutzeri, Klebsiella variicola, Citrobacter freundii, and Klebsiella variicola. Out of nine isolates, five were found resistant to 5 mM CuSO4 and decolourise Methylene Blue, Congo Red, and Basic Fuchsine dyes at a maximum concentration of 700 ppm.